Potential Therapeutic Targets in Triple-Negative Breast Cancer Based on Gene Regulatory Network Analysis: A Comprehensive Systems Biology Approach - Maryam Ahmadi; Neda Barkhoda; Aida Alizamir; Amir Taherkhani (International Journal of Breast Cancer)
Conclusion: This study provides insights into the molecular mechanisms of TNBC and suggests CHEK1, PLK1, and their upstream regulators as potential therapeutic targets for TNBC treatment.